Analysis of Online Learning Education Costs for Fisherman Children, Borimasunggu Village, Maros Regency - Agussalim, Agussalim Al Fath; Made, Sutinah; Fakhriyyah, Sitti; Arief, Andi Adri; Gosari, Benny Audy Jaya (PONGGAWA : Journal of Fisheries Socio-Economic, 2021)
This study aims to find out how much is incurred for the cost of education of fishermen's children before and during online learning and what percentage of spending is incurred on the education costs of fishermen's children from the total expenditure of fishermen's households. This research was carried out on December 10, 2020-11 Pktober 2021 in Borimasunggu Village of Maros Regency. The sampling method in this study was Purposive sampling. The data sources used are primary data and secondary data. Data analysis uses quantitative descriptive analysis by calculating the amount of income and expenditure by tabulating the data as well as the applicable analysis. Calculating the amount of fishermen's expenditure by summing up total food and non-food expenditures from before the pandemic and during the Covid-19 pandemic then analyzed the percentage of expenditures for education costs for fishermen's children with a percentage of 13.44% before the enactment of the online learning system and 7.25% during its enactment with learning methods used through gadgets with the WhatsApp application carried out by teachers to students who participated in activities. Learning to teach.